Monopolistic Practices by Google LLC through the Implementation of the Google Play Billing System (Case Study of KPPU Decision Number 03/KPPU-I/2024) - Azzahra, Dinda; Hutabarat, Sylvana Murni Deborah (Jurnal Daulat Hukum, 2025)
Digital businesses are growing along with technological advancements. As one of the largest technology companies in the world, Google controls more than 90% of the digital application distribution market share. Google has implemented a coercive Google Play Billing System, thus triggering monopolistic practices in the digital market. This study aims to analyze the form of monopolistic practices of Google LLC through the Google Play Billing System and examine its impact on business competition, technological innovation, application developers, and consumers in the Indonesian digital ecosystem. The research method uses normative juridical with a case study approach of Case Decision No. 03/KPPU-I/2024 through an analysis of statutory regulations. The results show that the implementation of the Google Play Billing System fulfills the elements of monopolistic practices as stipulated in Article 17 of Law No. 5 of 1999 through dominant market control, control of payment system access, and restrictions on consumer and developer choices. The impacts of the Google Play Billing System policy include increased developer operational costs, obstacles to innovation in alternative payment technologies, dependence on the Google ecosystem, and reduced consumer choices.